Evaluating Safety Attributes in Infrastructure Projects - Ammad, S. (Institute of Electrical and Electronics Engineers Inc., 2020)
Currently, the construction sector is considered to have significant economic impacts and one of the riskiest sectors. It is marked by a significant number of accidents and injuries, affecting production, efficiency, and harmful effects on society. A successful safety policy can prevent several construction site accidents. This study aims to investigate the safety management in infrastructure projects. A questionnaire survey for 30 professionals was conducted to identify variables that affect safety management in infrastructure projects. The obtained data were analysed statistically. The study suggests that health and safety innovation benefits include reduced injury risk, increased efficiency, better employee ties, and improved reputation through better safety management. Â© 2020 IEEE.